Analisis Kinerja Jalan Tengkuruk Permai dengan Mikrosimulasi Pemindahan Terminal dan Parkir Badan Jalan - Taharudin Subagyo; Melawaty Agustien; Joni Arliansyah (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2021)
Tengkuruk Permai street is currently used for city transportation terminals, on street parking, access and exit to 16 Ilir market parking lot (off street parking), entrance to Ampera Bridge, passenger access to LRT stations and Skate Park. The various functions of this street caused the reduction in street service levels at certain hours and become a congestion point in Palembang city. This study aims to obtain the results of the analysis of Tengkuruk Permai’s street performance in the scenario conditions of terminal relocation and on street parking. The data were collected directly by measuring and enumeration then micro-simulated with the Vissim software. Vissim microsimulation modeling is carried out in existing conditions and scenarios by combining the 3 (three) floors parking building construction plans, city transport routes, Tengkuruk Permai street which has been cleared of on street parking and terminals, street networks around the research location and intersection arrangements concurrently. The street performance analysis uses the calculation of the V/C ratio, where the calculation of the street capacity uses the Vissim microsimulation output such as speed, density and volume obtained in the link of segment evaluation menu. Capacity determination is using the calculation of relation of flow (q), velocity (v) and density (k). The scenario of relocating the city transport terminal and street parking to the 3 (three) floors parking building plan at 16 Ilir market parking lot can increase the capacity of Tengkuruk Permai Street from 1087,88 pcu/hour/direction to 2295.15 pcu/hour/direction and improve the service level from level E to level A.